2020
DOI: 10.3390/molecules25173836
|View full text |Cite
|
Sign up to set email alerts
|

A Nanofibrillated Cellulose-Based Electrothermal Aerogel Constructed with Carbon Nanotubes and Graphene

Abstract: Nanofibrillated cellulose (NFC) as an environmentally friendly substrate material has superiority for flexible electrothermal composite, while there is currently no research on porous NFC based electrothermal aerogel. Therefore, this work used NFC as a skeleton, combined with multi-walled carbon nanotubes (MWCNTs) and graphene (GP), to prepare NFC/MWCNTs/GP aerogel (CCGA) via a simple and economic freeze-drying method. The electrothermal CCGA was finally assembled after connecting CCGA with electrodes. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The MWCNTs/GP/CNFs mixture was ultrasonically dispersed and poured into Petri dishes. The cellulose-based electrothermal aerogels were prepared by freezing the MWCNTs/GP/CNFs mixture at −50 °C for 2 h and vacuum freeze-dried for 48 h . The controllable Joule heating performance and long-term heating stability of cellulose-based aerogels were studied using size, structure, and performance regulation. , Mixed solutions of an MXene and CNFs were poured into a mold with a certain thickness and then freeze-dried to obtain a controlled size and structure (Figure a–d).…”
Section: Production Methodsmentioning
confidence: 99%
“…The MWCNTs/GP/CNFs mixture was ultrasonically dispersed and poured into Petri dishes. The cellulose-based electrothermal aerogels were prepared by freezing the MWCNTs/GP/CNFs mixture at −50 °C for 2 h and vacuum freeze-dried for 48 h . The controllable Joule heating performance and long-term heating stability of cellulose-based aerogels were studied using size, structure, and performance regulation. , Mixed solutions of an MXene and CNFs were poured into a mold with a certain thickness and then freeze-dried to obtain a controlled size and structure (Figure a–d).…”
Section: Production Methodsmentioning
confidence: 99%
“…However, the enhanced dielectric constants were always at the expense of similar increases in loss, which was attributed to the motion of free charge carriers resulting from the formation of continuous conductive networks. Due to excellent electrical conductivity and thermal conductivity, graphene aerogel can be composited into the polymer matrix as a functional filler, thereby achieving application value in electrothermal field [111]. Yang et al [112] reported graphene aerogel/epoxy resin nanocomposites (EGAC) with excellent electrothermal properties.…”
Section: Electrical Properties and Applicationsmentioning
confidence: 99%
“…The dispersion of graphene in substrate is always particularly important for improving the performance of aerogel. In order to avoid aggregation induced by strong a van der Waals force, many preparation methods involving covalent and/or non-covalent modification between GO and polymer matrix and appropriate ultrasonic dispersion are employed [ 33 ]. The dispersion of graphene can be reflected on the morphology of aerogel characterized by SEM, SEM-EDS and TEM, and the XRD pattern.…”
Section: Preparation Strategiesmentioning
confidence: 99%